Home » Blog » Find the limit of the given function

Find the limit of the given function

Find the value of the following limit.

    \[ \lim_{x \to 0^+} \frac{1}{x \sqrt{x}} \left( a \arctan \frac{\sqrt{x}}{a} - b \arctan \frac{\sqrt{x}}{b} \right). \]


To simplify the computations, we make the substitution t = \sqrt{x}. Then,

    \[ \lim_{x \to 0^+} \frac{1}{x \sqrt{x}} \left( a \arctan \frac{\sqrt{x}}{a} - b \arctan \frac{\sqrt{x}}{b} \right) = \lim_{x \to 0^+} \frac{1}{t^3} \left( a \arctan \frac{t}{a} - b \arctan \frac{t}{b} \right). \]

Now, we apply L’Hopital’s rule three times,

    \begin{align*}  \lim_{t \to 0^+} \frac{1}{t^3} \left( a \arctan \frac{t}{a} - b \arctan \frac{t}{b} \right) &= \lim_{t \to 0^+} \frac{1}{3t^2} \left( \frac{a^2}{a^2+t^2} - \frac{b^2}{b^2+t^2} \right) \\[9pt]  &= \lim_{t \to 0^+} \frac{1}{6t} \left( \frac{-2a^2 t}{(a^2+t^2)^2} + \frac{2b^2 t}{(b^2+t^2)^2} \right) \\[9pt]  &= \lim_{x \to 0^+} \frac{1}{6} \left( \frac{-2a^2(a^2+t^2) + 8a^2 t^2}{(a^2+t^2)^3} + \frac{2b^2(b^2+t^2) - 8b^2 t^2}{(b^2+t^2)^3} \right) \\[9pt]  &= \frac{1}{6} \left( \frac{-2}{a^2} + \frac{2}{b^2} \right) \\[9pt]  &= \frac{1}{3} \left( \frac{a^2 - b^2}{(ab)^2} \right). \end{align*}

Since this limit exists, the application of L’Hopital’s rule was justified.

Point out an error, ask a question, offer an alternative solution (to use Latex type [latexpage] at the top of your comment):